SHORT AND LONG-TERM IMPACT OF EDUCATIONAL ENROLLMENT RATES ON ECONOMIC GROWTH: FOR INDONESIA'S SUSTAINABLE DEVELOPMENT OF HUMAN CAPITAL - Meilisa Meilisa; Elfindri Elfindri; Yulia Anas; Edi Ariyanto (Transpublika Publisher, 2024)
This research explores the relationship between Indonesia's economic growth and school participation rates. Using the ARDL model and Bounds test cointegration method, the study examines this relationship and finds that investing more in education, particularly at higher levels, can contribute to long-term economic growth. The study emphasizes the role of education in shaping human resources and promoting sustainable economic development. It suggests that increased investment in education can create a stronger pool of skilled workers, leading to economic growth. The research also reveals a temporary increase in employment as a result of education-driven growth, contributing to the sustainable development of human resources. The study highlights the importance of education funding in nurturing human capital and advocates for policy interventions that prioritize education as a driver of Indonesia's long-term development goals. Overall, this study emphasizes the transformative potential of investing in human capital for Indonesia's economy. In conclusion, this study sheds light on the relationship between economic growth and education, emphasizing the transformative potential of investing in human capital for the sustainable development of Indonesia's economy.